(untitled) (Scientific journal of the Fergana State University, 2024)
This article contains comments on the linguistic study of Navoi’s creativity. Including Navoi’s last epic "Khamsa" "Saddi Iskandariy", the fact that the poet as a poet wrote his works in Turkic and Persian languages, Persian-Tajik words used in the work, their semantics, a dictionary of meanings, Farsi-Tajik synonyms and antonyms, the use of superlatives, the activity of Arabic and Persian words in the use of superlatives. Opinions were also expressed on the use of conjunctions, pronouns and repetitions used in the works of Navoi. In addition, we are talking about the emergence of Persian izafet through word order; the izafet element in such compounds does not perform the function of grammar, but becomes an integral part of the lexical unit by connecting with one word.